TINJAUAN YURIDIS TERHADAP PERLINDUNGAN WARTAWAN DALAM PENGUNGKAPAN IDENTITAS NARASUMBER PELAKU MATCH FIXING - Hans Poliman; Adityo Saputra; Windisen Windisen (PROSIDING SERINA, 2021)
Sport is one of the priorities in advancing development at the national level, so that the field of sports has a very large role as an effort to make the name of the nation and state proud and promote national development, so that regulations regarding sports in the national legal system must be accountable, football has ranked first as a sport. However, the public's enthusiasm for football is not matched by the quality provided by the federation, namely the All-Indonesian Football Association (PSSI) in building a modern football industry and with integrity, one of the problems that has occurred from the past until now is match fixing. which is currently being hotly discussed on one of the television programs, namely the mata najwa program which has a topic entitled "PSSI BISA APA VOLUME 6". In the show, Najwa Shihab as the presenter of Mata Najwa conducted a teleconference with a referee who served in the Indonesian league 1 with the initials Mr. Y. who claimed to have participated in fixing the score in league 1, the aim of this research is to answer the current problems, among others, legal protection for journalists in keeping the identity of their sources secret and procedures for revealing identities in revealing match actors. fixing, the research method used in this study is normative juridical. The author concludes that journalists have the right to keep the identity of their sources secret, namely based on Article 1 point 10 and Article 4 paragraph 4 regarding the right to refuse in the Press Law, then in carrying out their profession journalists are also entitled to legal protection according to Article 8 of the Press Law, then if there are parties who want to disclose the identity of the match fixing resource person, there are 2 options that can be taken, the first, the resource person allowing/opening the identity voluntarily, and the second, through legal channels..